การพัฒนาเครื่องหมายไมโครแซเทลไลต์สำหรับเอคโตไมคอร์ไรซาเห็ดเผาะ Astraeus hygrometricus (Pers.) Morgan - วันทนี ทาทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Astraeus hygrometricus (Pers.) Morgan is commercially important and edible mushroom in Thailand. This species forms ectomycorrhizal associated with a wide range of economically important host trees in Dipterocarp forests. Until now, knowledge about above and below ground population genetic structure and reproduction in this species has not been reported yet. Population genetic research requires genetic markers that exhibit levels of variability appropriated for use in studies. Therefore, eleven co-dominant microsatellite markers were developed using an inter-simple sequence repeat (ISSR)-suppression- PCR technique. Four polymorphic loci, CA -05, GTC-01, GTC-04 and GTC-05, were characterized varying from two to seven alleles per locus. The observed and expected heterozygosites ranged from 0.025 to 0.175 and 0.275 to 0.450, respectively. The two microsatellite loci, CA-05 and GTC-05, did not amplify any other ectomycorrhizal species, indicating that they were species-specific markers. These microsatellite markers could be employed to investigate this ectomycorrhizae and mycelial aggregation in the soil. The polymorphic microsatellite markers obtained from this research could be used to investigate the population genetic structure and reproduction in this species for further studies. Furthermore, these markers could be used to monitor the environmental survival of this ectomycorrhizae after inoculated seedlings are transplanted into the site of plantations.